Modelo de diagnóstico de dificuldades de aprendizagem orientado a conceitos - Oliveira, Estêvão Domingos Soares de (2016)
The use of Virtual Learning Environments (VLE) in education has grown considerably in recent years, much due to the expansion of courses in distance mode. Such learning support spaces require you to think of new educational methods, particularly as regards the assessment of learning. Because of the large number of students in this type of education working in AVA, a large volume of data is generated. So to get yourself a good learning evaluation model, which offers the teacher possibilities for measuring student performance, it is necessary an analysis of such data. Moodle provides the teacher reports, charts and graphs that let you see the data for the actions of the students. Such actions represent from access to resources and materials, to participate in activities such as discussion forums and results of participation in questionnaires, for example. However, these Moodle native views do not take into account the real needs of teachers, especially in regard to effective monitoring of learning. Given the above, it is evident the need to have tools that help in this process. For this, there have to be a model permits, agile and flexible, storage and use of educational data of students to the application of techniques of Learning Analytics - measurement, collection, analysis and reporting of data on students and their contexts, for understanding and learning in order to optimize the environments in which they occur - with focus on diagnosis of learning disability situations in the context of the Distance Education. To evaluate this proposal, the ConcetpVis tool was implemented from the model proposed in this paper. Then, there was a case study in the Elementary Mathematics discipline of the Bachelor's Degree in Computer Education Unit Distance UFPB and finally presented a questionnaire to a group of teachers answered from his impressions.